Design and Kinematics Analysis of the Double Slider Tipping Bucket Mechanism - Zhu Jiacheng; Wei Zexu; Fang Mingjin; Meng Fanxi (Jixie chuandong)
In the process of on-pole rice noodles production,a new type of the tipping bucket mechanism is developed in order to meet the needs of continuous,fast,stable fetching and feeding. According to the function requirements of the tipping bucket mechanism,the corresponding design scheme is put forward. Through the comparison,the form of motion and transmission of tipping bucket mechanism is determined. Based on the motion mechanism of the tipping bucket mechanism,the motion model is established based on the movement of the mechanism,which is also called the double slider mechanism. On this basis,the kinematics analysis is carried out,and the change rules of the angle,angular velocity and angular acceleration with sliding block chain moved is derived. In the process of production,the motion equation of the tipping bucket is established to make the bucket rotate at a constant speed. The change rule of sliding block chain speed is obtained from the theory when the tipping bucket is used as the original moving part,and the kinematics parameters are provided for the intelligent control of the mechanism.